2017
DOI: 10.1002/adhm.201601182
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Nanoscale Encapsulation of Biofunctional Peptides to Enhance Bone Tissue Regeneration In Vivo

Abstract: Bone tissue healing is a dynamic process that is initiated by the recruitment of osteoprogenitor cells followed by their migration, proliferation, differentiation, and development of a mineralizing extracellular matrix. The work aims to manufacture a functionalized porous membrane that stimulates early events in bone healing for initiating a regenerative cascade. Layer‐by‐layer (LbL) assembly is proposed to modify the surface of osteoconductive electrospun meshes, based on poly(lactic‐co‐glycolic acid) and nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 55 publications
0
57
0
Order By: Relevance
“…It has been used alone or in combination with natural materials such as collagen or with growth factors to repair bone defects . Gentile et al reported that peptide‐functionalized nanolayered PLGA scaffolds provided molecular cues to bone marrow MSCs that enhance in vivo bone regeneration in a calvarial defect model . Pretreatment of stem cells is another strategy to improve cell differentiation into osteogenic lineage before adding the cells to a scaffold.…”
Section: Applications Of Advanced Biomaterials For Stem Cell Deliverymentioning
confidence: 99%
“…It has been used alone or in combination with natural materials such as collagen or with growth factors to repair bone defects . Gentile et al reported that peptide‐functionalized nanolayered PLGA scaffolds provided molecular cues to bone marrow MSCs that enhance in vivo bone regeneration in a calvarial defect model . Pretreatment of stem cells is another strategy to improve cell differentiation into osteogenic lineage before adding the cells to a scaffold.…”
Section: Applications Of Advanced Biomaterials For Stem Cell Deliverymentioning
confidence: 99%
“…Gentile et al deposited several polypeptides onto the electrospun mesh by LbL, and found that the osteogenic differentiation of the seeded mesenchymal stem cells was significantly improved. Implantation of functionalized electrospun mesh in skull defects can promote bone regeneration (Gentile et al, ). In summary, for 3D electrospinning scaffolds with complex nanostructures, LbL is a promising surface modification method.…”
Section: Biomodification Of 3d Nanofibrous Scaffoldsmentioning
confidence: 99%
“…A recent study on nanoencapsulation of functional biopeptides in electrospun poly(lactic‐co‐glycolic acid) and nanohydroxyapatite fibers using layer‐by‐layer approach showed increased matrix mineralization for bone tissue regeneration . The functional biopeptides are grafted into discrete nanolayers, which include KRSR (lysine‐arginine‐serine‐arginine) sequence to enhance cell adhesion and proliferation, NSPVNSKIPKACCVPTELSAI to guide bone marrow mesenchymal stem cells differentiation, and FHRRIKA (phenylalanine‐histidine‐arginine‐arginine‐isoleucine‐lysine‐alanine) to improve mineralization matrix formation . Studies show that pDA coating stabilizes MSC adhesion and proliferation and maintains the self‐renewal property of pluripotent stem cells for a long time .…”
Section: Factors Effecting Cell Adhesion and Proliferationmentioning
confidence: 99%
“…[20] The functional biopeptides are grafted into discrete nanolayers, which include KRSR (lysinearginine-serine-arginine) sequence to enhance cell adhesion and proliferation, NSPVNSKIPKACCVPTELSAI to guide bone marrow mesenchymal stem cells differentiation, and FHRRIKA (phenylalanine-histidine-arginine-arginine-isoleucine-lysine-alanine) to improve mineralization matrix formation. [21] Studies show that pDA coating stabilizes MSC adhesion and proliferation and maintains the self-renewal property of pluripotent stem cells for a long time. [22] The hydrophilicity of pDA coating increases the adhesion of cells to the substrate and also enhances the growth of the attached cells as compared to pristine scaffolds.…”
Section: Surface Coating/functionalizationmentioning
confidence: 99%